2017
DOI: 10.24874/ti.2017.39.02.15
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Ni–B Coating of Pure Titanium Surface for Enhanced Tribocorrosion Performance in Artificial Saliva and Antibacterial Activity

Abstract: A B S T R A C TIn the present study, the surface of commercial pure (Grade 2) titanium was coated with electroless Ni-B. The surface morphology, microstructure and phase identification were analysed by X-Ray Diffraction (XRD) and Field Emission Gun Scanning Electron Microscope (FEG-SEM) equipped with Energy Dispersive X-ray Spectroscopy (EDS). The tribocorrosion performance in a laboratory simulated artificial saliva was investigated using a reciprocating ballon-plate tribometer coupled to an electrochemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
6
0
1
Order By: Relevance
“…Finally it can be concluded that a hard and self-lubricating Ni-B coating also led to a reduction in the actual contact area resulting lower wear rate and friction coefficient ( Table 1). The cauliflower like surface morphology and nodular growth have been confirmed in several research works and the present observations corroborate well with them [17][18][19][20][21][22][23].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Finally it can be concluded that a hard and self-lubricating Ni-B coating also led to a reduction in the actual contact area resulting lower wear rate and friction coefficient ( Table 1). The cauliflower like surface morphology and nodular growth have been confirmed in several research works and the present observations corroborate well with them [17][18][19][20][21][22][23].…”
Section: Resultssupporting
confidence: 91%
“…Conversely, at low SEM magnifications a smoother surface was observed in the wear track for the coating (Figure 5 c). At high magnification ( Figure 5 d), it is possible to observe that flattening occurred for some nodules while others remained almost undamaged, as reported by previous studies [18,21]. The flattening areas revealed the nodular grain growth of the Ni-B coating.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Nickel is a preferred metal in this method for producing coatings. Nickel coatings have excellent corrosion and wear resistance and high microhardness [1]. The necessity for the materials surface properties improvement launched the idea of the various second phase particles incorporation in the electroless nickel coatings in the 1960s [2] and led to the development of electroless nickel composite coatings.…”
Section: Introductionmentioning
confidence: 99%